A novel reverse helical milling process for reducing push-out delamination of CFRP. (1st December 2020) - Yang, Guolin; Dong, Zhigang; Gao, Shang; Bao, Yan; Kang, Renke; Guo, Dongming
Abstract: When drilling Carbon fiber reinforced plastic (CFRP), delamination can be found at hole-exit frequently, which is known as typical machining damage and would weaken the mechanical strength of finished components. The occurrence of delamination is regarded as the consequence of the deformation of uncut material that caused by thrust force. This study aims to propose a new reverse helical milling (RHM) method to restrain the delamination, in which, the principle of reducing the deformation extent of uncut material is via material rigidity enhancement. Firstly, two-dimensional analysis was used to contribute the avoidance of push-out delamination during CFRP drilling. Then, considering both CFRP and metal-CFRP stacks, an idea of reversing feed direction of cutting tool is processed, which enhances the rigidity of uncut material by means of either increasing the uncut thickness or providing an equivalent back-up without employing any extra facility. In order to realize reverse cutting without changing the original position of both workpiece and machine equipment, special cutting tools and detailed operation steps are designed. Finally, confirmatory experiments were carried out and the results demonstrated that RHM will neither deteriorate the existing delamination nor generate new ones and as a result, the push-out delamination was effectively reduced.